FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN SISTEM PEMBAYARAN GO-PAY TERHADAP INTENSITAS PENGGUNAAN LAYANAN GOJEK DI SAMARINDA - Lewi Patabang; Noor Fachman Tjetje (Jurnal Eksis, 2021)
This study aims to determine the variables of benefit, convenience, risk, and promotion impact the attitudes of Go-pay users, as well as to determine the effect of Go-pay users' attitude variables on the intensity of using Gojek services in Samarinda. The data used is primary data sourced from Go-pay users in the city of Samarinda and secondary data sourced from the internet, websites, articles, and news. The sample used in this study amounted to 149 respondents. This study uses a tool to process data, namely SPSS (Statistical Product Service Solution). This testing process uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, simple linear regression analysis, T-test, F test, and R2 test. The results of this study indicate that the variables of benefit, convenience, and promotion have a positive and significant effect on the attitudes of Go-pay users, and the risk variable has a negative and insignificant effect on the attitudes of Go-pay users. While the Go-pay user attitude variable to the intensity of using Gojek services has a positive and significant effect. Keywords: Usefullness, Ease of Use, Attitude, Risk, Promotion, and Intensity of Using Gojek Services